ANALYSIS VEGETATION OF SHADE CORPSE FLOWER (Amorphophallus paeoniifolius (Dennst.) Nicholson) in PADANG TIJI SUB-DISTRICT of PIDIE DISTRICT - Mulyati Mulyati; Djufri Djufri; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
ABSTRACTCorpse flower (Amorphophallus paeoniifolius) is one of the seasonal herbaceous plants including familia Araceae that can grow well in the shade. The shade of vegetation can be used as the corpse flower habitat preferences in the region, making it easier to know the population of the largest corpse flower under the shade of vegetation. This study aims to determine the type of vegetation that the shelter and to find out how the diversity index of vegetation corpse flower shade in the Padang Tiji sub-district of Pidie district. The Research was done by finding the whereabouts of the corpse flower in Padang Tiji to key persons at the altitude of 200, 400 and 600, so it can be done later retrieval corpse flower shade vegetation data using squares method. At each elevation laid five plots area of each plot was 10 m x 10 m. Based on the analysis of vegetation that houses the corpse flower, found as many as 20 species from 11 familia. Corpse flower is found in the shade of a tree Sterculia alata and Areca catechu, so that both species have the highest among other species on the third altitude. Additionally, Leea aequata and Eupatorium odoratum are also shade of vegetation that were dominant at the three altitudes for the habitus of shrubs / bushes. Thus, the corpse flower shade preferences can be known from the type of vegetation shading. Vegetation diversity index auspices of the corpse flower has a lower category either on habitus trees or shrubs / bushes.Keywords: the corpse flower, vegetation, shade, diversity index.